2012
DOI: 10.1111/j.1467-7652.2012.00742.x
|View full text |Cite
|
Sign up to set email alerts
|

Utility of the P19 suppressor of gene‐silencing protein for production of therapeutic antibodies in Nicotiana expression hosts

Abstract: SummaryTo study how the P19 suppressor of gene-silencing protein can be used effectively for the production of therapeutic glycoproteins, the following factors were examined: the genetic elements used for expressing recombinant proteins; the effect of different P19 concentrations; compatibility of P19 with various Nicotiana tabacum cultivars for transgenic expression; the glycan profile of a recombinant therapeutic glycoprotein co-expressed with P19 in an RNAibased glycomodified Nicotiana benthamiana expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(70 citation statements)
references
References 40 publications
0
64
0
Order By: Relevance
“…On day 5 post infiltration, some slight discoloration was detected mostly in the younger leaves (Figure 8C). Notably, p19 infiltrated tissue yielded higher amounts of GFP compared to mock-infiltrated tissue, contrary to the results obtained with p19 from TBSV [48]. …”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…On day 5 post infiltration, some slight discoloration was detected mostly in the younger leaves (Figure 8C). Notably, p19 infiltrated tissue yielded higher amounts of GFP compared to mock-infiltrated tissue, contrary to the results obtained with p19 from TBSV [48]. …”
Section: Resultsmentioning
confidence: 60%
“…It has been previously shown that p19 from tomato bushy stunt virus (TBSV) induces a hypersensitive response in tobacco cv. I64 infiltrated tissue which not only reduces the biomass yield of tobacco plants but also negatively affects the accumulation levels of co-expressed proteins starting at 3 dpi [47,48]. We monitored infiltrated 81V9 and I64 leaves from 2 to 5 dpi, and did not observe any discoloration or other signs of necrosis before 5 dpi.…”
Section: Resultsmentioning
confidence: 99%
“…Wild-type (P35S:MSL10-GFP), phosphomimetic (P35S:MSL10 D -GFP), or alanine substitution (P35S:MSL10 A -GFP) versions of MSL10 were transiently overexpressed in tobacco leaves via infiltration with Agrobacterium tumefaciens transformed with the binary vector pK7FWG2 (Karimi et al, 2002) harboring the appropriate MSL10 sequences. A plasmid encoding the p19 gene of tomato bushy stunt virus, which is often used in transient expression systems to inhibit transgene silencing (Voinnet et al, 2003;Waadt and Kudla, 2008;Garabagi et al, 2012), was coinfiltrated with each construct. Three days after infiltration, successful expression was confirmed through GFP fluorescence ( Figure 3A, top row).…”
Section: The Phosphorylation State Of the Msl10 N-terminal Domain Regmentioning
confidence: 99%
“…Plantspecific N-glycosylation, an important productspecific and application-specific issue for antibodies made in plants, has been addressed using classical genetic engineering approaches [163][164][165][166] as well as more recent genome editing technologies. 167 A number of auxiliary technologies have been used to address post-transcriptional gene silencing, 168 target protein folding and proteolysis, [169][170][171] and downstream processing strategies for extraction, clarification, and purification. 172 Manufacturing capacity is being built at several international locations (Table 2) and models predicting the manufacturing costs are being refined.…”
Section: Translating Green Bionanomaterials Into Green Bionanomedicinesmentioning
confidence: 99%